Implementing Student Led Conference (SLC)-Based Learning Reflection in Teaching and Learning Process: A Case in an Islamic Primary School - Khoeriyah, Faizatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Student Led Conferences (SLC) have emerged as a transformative approach to student reflection and goal setting, fostering a collaborative learning environment that empowers students to take ownership of their educational journey. This qualitative study delves into the implementation of SLC at SD Islam Al Azhar 60 Pekalongan, exploring its impact on students, teachers, and parents. Employing a qualitative descriptive approach, the study encompasses observations, interviews, and documentation to gather data from 25 students and 2 teachers in Class 1B. Data analysis follows the interactive model of Miles, Huberman & Saldana, involving data condensation, data display, and conclusion drawing. The findings reveal that SLC implementation provides a valuable platform for students, teachers, and parents to assess student progress and identify areas for improvement. SLC enables teachers to gain insights into individual student development, while parents gain a deeper understanding of their children's strengths, challenges, and aspirations. SLC empowers students to take charge of their learning by allowing them to select topics of interest for presentation. This fosters self-directed learning, encouraging students to delve deeper into subjects that resonate with them. Moreover, SLC facilitates open communication among stakeholders, fostering a sense of shared responsibility for student success. Teachers and parents gain valuable insights into students' learning experiences, enabling them to provide tailored support and guidance. SLC implementation at SD Islam Al Azhar 60 Pekalongan exemplifies the transformative power of student-centered approaches. By empowering students to take ownership of their learning, SLC cultivates a collaborative environment that nurtures academic growth, personal development, and lifelong learning.